Finite element analysis of coil spring of a motorcycle suspension system using different fibre materials. (2020) - Sreenivasan, M.; Dinesh Kumar, M.; Krishna, Ram; Mohanraj, T.; Suresh, G.; Hemanth Kumar, D.; Sai Charan, A.
Abstract: This research work emphasis on analyzing and evaluating the performance of coil spring suspension system of a motorcycle made of different fibre materials. Design of suspension system carried out through Autodesk Inventor for an existing suspension system of a motorcycle. Finite Element Analysis (FEA) carried out through Ansys 16.0 software. Applying different loads with respect to payload of the motorcycle, comparative structural analysis have been carried out to determine the total deformation, stress and strain of the suspension at static conditions. Analysis results concludes that E-Glass Fibre is an optimal fibre material for coil springs that was less deformed, less stressed and is safer than other materials on applied loads.